Assessment of Community Engagement and Success of Education Projects in Tanzania: A Case of Changarawe Village, Morogoro - Eliza Mwakasangula (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
Education has been a global agenda that has been promoted by countries and different international agencies. Various countries including Tanzania have been implementing various programmes and projects to promote the education sector. Community engagement has been claimed to be vital in success of these projects. However, factors promoting community engagement and methods used to engage community members in education projects in Tanzania have not been well captured in the literature. Social capital theory was used to guide the study. Data was collected from Changarawe village in Morogoro. The study used a descriptive research design. Qualitative approach was used to collect data from 14 respondents by using interviews and focus group discussion as tools of data collection. Purposive sampling technique was used to obtain a sample of 14 participants for interviews and 9 participants for focus group discussions which made a sample size of 23 for the study.  Thematic analysis was used to analyze collected data.   The study found community engagement is enhanced to the large extent by leaders in the study area. Moreover, significance of the projects was found to play an important role in enhancing community engagement. Various methods of engaging community members were found through five major themes which are village meetings, sports and games, social media networks, phone calls and door-to-door. The study recommends community members to be engaged throughout the project cycle and multiple methods of engaging the community has to be used to increase level of community engagement in education and other related development projects